The distribution of stresses and strains in the mating elements disk tools working bodies of roadheaders; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Khoreshok A. A. Aleksey Alekseevich; Mametyev L. E.; Borisov A. Yu.; Vorobyev A. V. Aleksey Vasilievich (Advanced technologies and equipment for agro-industrial complex (AIC) and mining, 2015)
Title screen